2021
DOI: 10.1186/s13104-021-05557-0
|View full text |Cite
|
Sign up to set email alerts
|

Snail mucus from the mantle and foot of two land snails, Lissachatina fulica and Hemiplecta distincta, exhibits different protein profile and biological activity

Abstract: Objective Snails secrete different types of mucus that serve several functions, and are increasingly being exploited for medical and cosmetic applications. In this study, we explored the protein pattern and compared the biological properties of the mucus secreted from the mantle collar and foot of two snail species, Lissachatina fulica and Hemiplecta distincta. Result Protein profile showed a different pattern between the two species and between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Previous in vitro studies using the minimal inhibitory concentration assay showed Staphylococcus aureus (S. aureus) growth suppression, another potential pathogen related to AV. 19,20 Lastly, our study did not control the type of face mask, which might interfere with the maskne severity.…”
Section: Ta B L E 1 Demographic and Baseline Characteristic Datamentioning
confidence: 97%
“…Previous in vitro studies using the minimal inhibitory concentration assay showed Staphylococcus aureus (S. aureus) growth suppression, another potential pathogen related to AV. 19,20 Lastly, our study did not control the type of face mask, which might interfere with the maskne severity.…”
Section: Ta B L E 1 Demographic and Baseline Characteristic Datamentioning
confidence: 97%
“…Pitt et al showed that the mucosa of H. aspersa (Cornu aspersum) was effective against three laboratory strains of P. aeruginosa [30]. In addition, antibacterial proteins and glycoproteins have been reported in the mucus of various terrestrial snails (A. fulica, H. aspersa, Cryptozona bistrialis, Lissachatina fulica, and Hemiplecta differenta) [18,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Mucuses are hydrogels and viscous liquids secreted by animals that act as adhesives, lubricants, semi-permeable barriers, and mineralizing agents. , Because of nature’s widespread reliance on mucuses to fill many essential functions, researchers are exploring animal-sourced mucusessuch as porcine gastric mucus or snail mucus , for addressing myriad soft-material needs, including as moisturizers in cosmetics, for coating surgical implants to mitigate rejection, , as cell growth media for tissue repair, as dermal patches, for cartilage lubrication, as antiviral and antimicrobial coatings, , as drug delivery agents, and as scaffolding for cell culture . However, the complex purification, , batch-to-batch variability, and potential for parasite contamination of these natural substances often lead to issues such as structural degradation and inconsistency of their advantageous material and biological properties, and potential toxicity.…”
Section: Introductionmentioning
confidence: 99%